Transformation education Pancasila as vehicle systematic education character in the era of globalization: A study conceptual – philosophical - Jackson Simamora; Dasim Budimansyah; Encep Syarief Nurdin; Mupid Hidayat (Universitas Muhammadiyah Malang, 2025)
Pancasila education plays an important role in shaping a strong and competitive national character in the era of globalization. This study aims to analyze the transformation of Pancasila education in the character education curriculum and its implications for the formation of national identity and morals of the younger generation. This study used a qualitative exploratory approach to collect data from various primary and secondary sources, including interviews with academics, practitioners, and education policymakers. The analysis was conducted using NVivo 12 software to identify patterns and main themes in the discussions. The study results indicate that Pancasila education not only functions as an instrument of state ideology but also as a dynamic paradigm that accommodates cultural diversity and global challenges. The implementation of Pancasila education in the curriculum must be more reflective, interactive, and experience-based students' to encourage students' critical thinking and social awareness. Despite facing challenges in adapting to changing times and technological developments, Pancasila education remains relevant as the main foundation for building national character. Collaboration between the government, academics, and the community is needed to develop innovative and contextual learning methods so that Pancasila values ​​can continue to be internalized in everyday life.